2020
DOI: 10.3390/f11080855
|View full text |Cite
|
Sign up to set email alerts
|

Mice and Habitat Complexity Attract Carnivorans to Recently Burnt Forests

Abstract: Faunal responses to wildfire depend on the fire effects on direct mortality, habitat structure, and resource availability for animals. Despite the importance of large predators in terrestrial trophic webs, little is still known about how fire affects carnivorans (the mammalian order Carnivora). To evaluate the responses of the carnivoran community to fire, we studied three recently burnt forest areas in the western Mediterranean basin. Line transects were used to quantify evidence of carnivorans (mainly feces)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
(91 reference statements)
3
9
0
Order By: Relevance
“…Fox relative abundance was greatest in the recently‐burnt growth stage, a finding consistent with a growing body of evidence suggesting positive relationships between foxes and fire (Hradsky, 2020; Puig‐Gironès & Pons, 2020). For example, telemetry studies have shown that foxes intensified their use of recently‐burnt sites within their home ranges (Hradsky et al ., 2017 b ), and research in open forest 50‐km south of our study area found that fox relative abundance was substantially higher immediately post‐fire compared to pre‐fire (Robley et al ., 2016).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Fox relative abundance was greatest in the recently‐burnt growth stage, a finding consistent with a growing body of evidence suggesting positive relationships between foxes and fire (Hradsky, 2020; Puig‐Gironès & Pons, 2020). For example, telemetry studies have shown that foxes intensified their use of recently‐burnt sites within their home ranges (Hradsky et al ., 2017 b ), and research in open forest 50‐km south of our study area found that fox relative abundance was substantially higher immediately post‐fire compared to pre‐fire (Robley et al ., 2016).…”
Section: Discussionsupporting
confidence: 80%
“…Conceptually, associations between fire, important resources, predators and native mammals include indirect fire effects, where native species respond to fire via the effect that it has on resource availability or predators (Hradsky et al ., 2017 a ; Geary et al ., 2018; Parkins, York & Di Stefano, 2018; Puig‐Gironès & Pons, 2020). Nevertheless, we are aware of only two other studies that have quantified an indirect fire effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, predators have responded primarily to the abundance of small mammalian prey post‐fire and have shown little association with each other (e.g. Puig‐Gironès & Pons, 2020).…”
Section: How and Why Do Predators Respond To Fire?mentioning
confidence: 99%